Archivists, Librarians, and Theatre Research - Marini, Francesca (Archivaria, 2007)
This article is a partial report on the author’s three-year (2002–2005) study entitled Sources and Methodology of Theater Research in the View of Scholars and Information Professionals, which provided a picture of theatre research from the points of view of theatre scholars and of performing arts archivists and librarians. The study addressed, within the limits of the sample analyzed, the diversity of interests, approaches, and sources used in theatre research, the role and characteristics of the work of archivists and librarians in this context, and the interaction between these groups. From the study, it emerged that theatre scholars, performing arts archivists and librarians share many similarities, and that what they do may provide powerful tools for addressing many issues that are at the forefront of archival science, such as the proliferation of dynamic and interactive media and sources. RÉSUMÉ Cet article est un rapport partiel d’une étude menée par l’auteure pendant trois ans (2002-2005), intitulée Sources and Methodology of Theatre Research in the View of Scholars and Information Professionals, qui a permis de brosser un tableau de la recherche dans le domaine du théâtre, du point de vue des chercheurs, des archivistes et des bibliothécaires des arts de la scène. Cette étude abordait, autant que le permettait l’échantillonage établi, la diversité des intérêts, des approches et des sources utilisés pour la recherche dans le domaine du théâtre, le rôle et les caractéristiques du travail des archivistes et des bibliothécaires dans ce contexte, et l’intéraction entre ces deux groupes. Elle concluait que les chercheurs, les archivistes et les bibliothécaires des arts de la scène ont plusieurs points en commun, et que le travail qu’ils font fournit des outils importants pour aborder plusieurs points essentiels qui relèvent des sciences de l’archivistique, telle que la prolifération des médias et des sources dynamiques et interactives.